The Tróia Peninsula: an Aeolian Sedimentological Legacy - Neto, Carlos (2021)
The integration of studies from fields, such as geomorphology, palynology, history, archaeology and phytogeography, enables assessing the genesis and evolution of the most prominent Portuguese sand spit—the Tróia Peninsula. Data suggests that the spit has formed from Grimaldian dunes converted into barrier islands during the Holocene transgression, and coalesced by the accumulation of sediments transported by the northbound longshore drift. The Tróia Peninsula is integrated in one of the most important Portuguese natural protected areas. It holds a set of flora and vegetation of paramount relevance towards protection and conservation in accordance with the Natura 2000 Network. Its position acts as a barrier against the Atlantic Ocean, having allowed the development of the Sado estuary lagoon, which contains mud flats and salt marsh ecosystems, habitats for a wide range of flora and fauna, some of which with special protection status. The Tróia Peninsula forms indeed a natural protective barrier for the Natural Reserve of the Sado Estuary. The genesis of the peninsula, discussed in the present work, combined with the fact that it is made up exclusively of sand, make it very vulnerable to environmental changes, including sea level rise.